Integrating the Tetrapreneur Framework for Enhanced Halal Regulation - Devi, Yuliani Sari; Fatimah, P. L. Rika (Fakultas Ekonomi, UIN Maliki Malang, 2025)
This research presents how to maximize the implementation of Government Regulation No. 42 of 2024 concerning implementing Halal Product Assurance (JPH) with a Tetrapreneur theory approach. The Tetrapreneur theory is a new framework built from 4 pillars, Chainpreneur (Tetra I), Marketpreneur (Tetra II), Qualitypreneur (Tetra III), and Brandpreneur (Tetra IV). By using this theoretical approach, this study offers practical strategies for implementing PP No. 42 of 2024 and offers valuable insights for policymakers and stakeholders to improve the halal certification process in Indonesia. To achieve its objectives, the research uses a descriptive qualitative method that focuses on secondary sources by reviewing regulation research papers, books, journals, and relevant articles.